Cover Feature: Efficient Radical‐Enhanced Intersystem Crossing in an NDI‐TEMPO Dyad: Photophysics, Electron Spin Polarization, and Application in Photodynamic Therapy (Chem. Eur. J. 70/2018). Issue 70 (4th December 2018) - Wang, Zhijia; Gao, Yuting; Hussain, Mushraf; Kundu, Sushma; Rane, Vinayak; Hayvali, Mustafa; Yildiz, Elif Akhüseyin; Zhao, Jianzhang; Yaglioglu, Halime Gul; Das, Ranjan; Luo, Liang; Li, Jianfeng
Abstract : A stable radical (2, 2, 6, 6‐tetramethylpiperidinyloxy; TEMPO) was labeled with the visible‐light‐harvesting chromophore naphthalenediimide (NDI) to give an NDI‐TEMPO dyad. A detailed photophysical study shows efficient radical enhanced intersystem crossing (EISC; 74%), long‐lived triplet state of NDI (8.7 μs), quartet state formation (spin quantum number, S =3/2), and inversion of the electron spin polarization. This red‐light absorption, heavy‐atom‐free dyad NDI‐TEMPO has been used in photodynamic therapy, and hence opens new avenues of real applications of EISC systems. More information can be found in the Full Paper by J. Zhao, H. G. Yaglioglu, R. Das, L. Luo, J. Li, et al. onpage 18663 .